Penerapan Hygiene Dan Sanitasi Untuk Menjaga Kualitas Minuman Di Bar Restoran Bias Country Bali - Wisnawa, I Made Tresna; Dewi Irwanti, Ni Ketut; Induyoga Aditama, I Wayan (HARMONY HOSPITALITY, 2024)
The final assignment report entitled Application of Hygiene and Sanitation to Maintain the Quality of Drinks at the Bias Courtyard Bali Restaurant Bar, aims to determine the application of hygiene and sanitation to maintain the quality of drinks at the Bias Courtyard Bali Restaurant Bar, the obstacles faced when implementing hygiene and sanitation, and the efforts made to ensure that hygiene and sanitation are implemented well. qualitative descriptive research method obtained from two data sources, namely primary data and secondary data, as well as data collection techniques using observation, interviews and documentation. Hygiene and Sanitation is a preventive health effort that focuses its activities on individual activities and the human environment. Based on the discussion outlined by the author regarding the application of hygiene and sanitation to maintain the quality of drinks at the bar, the application of hygiene and sanitation at the Bias Courtyard Restaurant Bar is the same as the theory of the experts mentioned. This research produces 3 conclusions (1). The implementation of hygiene and sanitation has not been implemented properly due to the absence of written SOPs in the Bias Courtyard Restaurant Bar; (2). Obstacles that hinder the implementation of hygiene and sanitation include staff's lack of awareness of the importance of implementing hygiene and sanitation; (3). Efforts made to ensure that the implementation of hygiene and sanitation runs well are by holding briefings, training and directly controlling the operations at the bar. Based on these conclusions, it can be recommended that beverage processing must be carried out according to established SOPs, such as using hand gloves and washing beverage ingredients before using them to maintain hygiene and sanitation to maintain the quality of a beverage